High-strength steel sheet and method for producing same, and member and method for producing same

CN119654435APending Publication Date: 2025-03-18JFE STEEL CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380060103.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-29
Filing Date
2023-07-25
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to process high-strength steel plates with a yield strength of 800 MPa or above into automotive parts, and at the same time, excellent endurance and crack-resistance are required during collisions.

Method used

By controlling the composition and microstructure of the steel plate, the diffusible hydrogen in the steel is less than 0.50 mass ppm, the proportion of specific elements in the composition is also formed, and through heat treatment and surface light rolling and other processes, a reasonable ratio between the structure A with a nanohardness of 7 GPa or above and the structure B with a nanohardness of 6 GPa or below is improved, and the processability and collision endurance of the steel plate are improved.

Benefits of technology

It realizes good machining, excellent collision endurance and crack resistance of high-strength steel plates, and is suitable for the manufacturing of automotive parts and helps to achieve lightweight of the vehicle body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119654435A_ABST
    Figure CN119654435A_ABST
Patent Text Reader

Abstract

Provided is a high-strength steel sheet which has a yield strength of 800 MPa or more and which has excellent workability, impact resistance and crack resistance. The amount of diffusible hydrogen in the steel is 0.50 ppm by mass or less. The steel sheet has a component composition containing, in mass%, 0.150 to 0.500% of C, 0.01 to 3.00% of Si, 1.50 to 4.00% of Mn, 0.100% or less of P, 0.0200% or less of S, 0.100% or less of Al, 0.0100% or less of N, and 0.0100% or less of O, with the balance being Fe and unavoidable impurities. The total area ratio of tempered martensite and bainite is 55-95%, the abundance ratio (A / B) of a structure A having a nanohardness of 7 GPa or more and a structure B having a nanohardness of 6 GPa or less is 0.8-2.5, and the solid solution carbon concentration in the retained austenite is 0.50-0.90 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a high-strength steel plate having a yield strength (YS) of 800 MPa or more, a method for producing the same, and a component and a method for producing the same. Background Art

[0002] In recent years, for example, in the automobile industry, there has been a demand for improving the fuel efficiency of automobiles in order to reduce carbon dioxide (CO 2 ) emissions from the viewpoint of protecting the global environment.

[0003] In order to improve the fuel efficiency of automobiles, it is effective to seek to reduce the weight of the vehicle body, but in this case, it is necessary to seek to reduce the weight of the vehicle body while maintaining the strength of the vehicle body. If the steel plates that become automobile parts can be made stronger and the structure of the vehicle body can be simplified to reduce the number of parts, the weight of the vehicle body can be reduced.

[0004] For example, Patent Documents 1 to 3 disclose high-strength steel sheets having a yield strength of 800 MPa or more.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-21231

[0008] Patent Document 2: Japanese Patent No. 2018-21233

[0009] Patent Document 3: Japanese Patent No. 2017-214647 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In order to form a high-strength steel sheet having a yield strength of 800 MPa or more into an automobile part, good workability is required.

[0012] Furthermore, steel sheets used as automobile parts are also required to have excellent resistance during collision (hereinafter referred to as "collision resistance") and to suppress the progress of cracks caused by external forces during collision (excellent crack arrestability).

[0013] Therefore, an object of the present invention is to provide a high-strength steel sheet having a yield strength of 800 MPa or more and excellent in workability, impact resistance, and crack arrestability.

[0014] Methods used to solve problems

[0015] The present inventors have found that the above-mentioned object can be achieved by adopting the following configuration, thereby completing the present invention.

[0016] That is, the present invention provides the following [1] to

[10] .

[0017] [1] A high-strength steel sheet comprising a steel sheet having a diffusible hydrogen content of 0.50 mass ppm or less in steel, the steel sheet having a component composition and a microstructure, the component composition comprising, in mass %, C: 0.150 to 0.500%, Si: 0.01 to 3.00%, Mn: 1.50 to 4.00%, P: 0.100% or less, S: 0.0200% or less, Al: 0.100% or less, N: 0.0100% or less, and O: 0.0100% or less, with the balance being Fe and inevitable impurities, wherein in the microstructure, a total area ratio of tempered martensite and bainite is 55 to 95%, an abundance ratio A / B of a structure A having a nanohardness of 7 GPa or more to a structure B having a nanohardness of 6 GPa or less is 0.8 to 2.5, and a solid solution carbon concentration in retained austenite is 0.50 to 0.90 mass %.

[0018] [2] The high-strength steel sheet according to [1], wherein the chemical composition further contains, in mass %, at least one element selected from the group consisting of B: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less, Mo: 1.000% or less, Cr: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Zr: 0.1000% or less, Te: 0.100% or less, Cu: 1.000% or less, Ni: 1.000% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

[0019] [3] The high-strength steel sheet according to [1] or [2], further comprising a plating layer on the surface of the steel sheet.

[0020] [4] The high-strength steel sheet according to [3] above, wherein the coating layer is a hot-dip galvanized layer, an alloyed hot-dip galvanized layer, or an electrogalvanized layer.

[0021] [5] A method for manufacturing a high-strength steel sheet, which is a method for manufacturing the high-strength steel sheet described in [1] above, wherein a steel billet having the component composition described in [1] above is hot rolled to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is cold rolled to obtain a cold-rolled steel sheet, the cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950°C for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120°C or more and less than 280°C, and then heated to a reheating temperature T3, re-cooled without being held at the reheating temperature T3, and held at a temperature T4 lower than the reheating temperature T3 for more than 1 second, a heat input influence index J from the cooling stop temperature T2 to the reheating temperature T3 represented by the following formula (1) is 1500 to 4000, and the cold-rolled steel sheet after being held at the temperature T4 is subjected to surface temper rolling using a roller having a surface roughness of 1.5 to 5.0 μm.

[0022] J = (T3-T2)(log(9t)+20) …(1)

[0023] In the above formula (1), t is the heating time from the above cooling stop temperature T2 to the above reheating temperature T3°C, and the unit is s.

[0024] [6] A method for manufacturing a high-strength steel sheet, which is a method for manufacturing the high-strength steel sheet described in [2] above, wherein a steel billet having the component composition described in [2] above is hot rolled to obtain a hot-rolled steel sheet, the hot-rolled steel sheet is cold rolled to obtain a cold-rolled steel sheet, the cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950°C for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120°C or more and less than 280°C, and then heated to a reheating temperature T3, re-cooled without being held at the reheating temperature T3, and held at a temperature T4 lower than the reheating temperature T3 for more than 1 second, a heat input influence index J from the cooling stop temperature T2 to the reheating temperature T3 represented by the following formula (1) is 1500 to 4000, and the cold-rolled steel sheet after being held at the temperature T4 is subjected to surface temper rolling using a roller having a surface roughness of 1.5 to 5.0 μm.

[0025] J = (T3-T2)(log(9t)+20) …(1)

[0026] In the above formula (1), t is the heating time from the above cooling stop temperature T2 to the above reheating temperature T3°C, and the unit is s.

[0027] [7] The method for producing a high-strength steel sheet according to [5] or [6] above, wherein the cold-rolled steel sheet is subjected to a plating treatment.

[0028] [8] The method for producing a high-strength steel sheet according to [7] above, wherein the coating treatment is hot-dip galvanizing, alloyed hot-dip galvanizing or electrogalvanizing.

[0029] [9] A member formed using the high-strength steel sheet according to any one of [1] to [4] above.

[0030]

[10] A method for manufacturing a component, comprising: subjecting the high-strength steel sheet according to any one of [1] to [4] above to at least one of a forming process and a joining process to obtain the component.

[0031] Effects of the Invention

[0032] According to the present invention, it is possible to provide a high-strength steel sheet having a yield strength of 800 MPa or more and excellent in workability, impact resistance, and crack arrestability. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a diagram showing an example of heat treatment.

[0034] Figure 2A is a cross-sectional view showing a cap member.

[0035] Figure 2B : is a schematic diagram showing a cap member provided for a three-point bending test. DETAILED DESCRIPTION

[0036] [High-strength steel plate]

[0037] The high-strength steel sheet according to the present embodiment (hereinafter also referred to as “the present high-strength steel sheet”) includes a steel sheet, and as described later, may further include a plating layer on the surface of the steel sheet.

[0038] The steel sheet included in the present high-strength steel sheet has a component composition and a microstructure described below, and satisfies the amount of diffusible hydrogen in steel described below.

[0039] High strength means that the yield strength (YS) is 800 MPa or more.

[0040] The high-strength steel sheet has a yield strength of 800 MPa or more and is excellent in workability, collision resistance and crack arrestability. Therefore, since the strength against collision is sufficient, it is suitable for use as a component of a transportation vehicle such as an automobile.

[0041] As a method of forming the present high-strength steel sheet, general processing methods such as press working can be used without limitation. As a method of welding the present high-strength steel sheet, general welding methods such as spot welding and arc welding can be used without limitation.

[0042] <Steel Plate>

[0043] First, the steel sheet included in the present high-strength steel sheet will be described.

[0044] The thickness of the steel plate is not particularly limited, and is, for example, 0.5 mm or more and 3.0 mm or less.

[0045] 《Ingredients》

[0046] The chemical composition of the steel sheet included in the present high-strength steel sheet (hereinafter, also referred to as “present chemical composition” for convenience) will be described.

[0047] Unless otherwise specified, "%" in the present component composition means "mass %".

[0048] (C: 0.150~0.500%)

[0049] C generates martensite and increases the strength of the steel sheet. When the amount of C is too small, the total area ratio of tempered martensite and bainite decreases, so the collision resistance and yield strength decrease. Therefore, the amount of C is 0.150% or more, preferably 0.180% or more, and more preferably 0.200% or more.

[0050] On the other hand, when the amount of C is too much, the structure A with a nanohardness of 7 GPa or more, which becomes the starting point of cracks, increases, so the workability decreases. Therefore, the amount of C is 0.500% or less, preferably 0.460% or less, and more preferably 0.400% or less.

[0051] (Si: 0.01~3.00%)

[0052] Si inhibits the formation of carbides during heat treatment, and affects the hardness of the structure and the solid solution carbon concentration in the retained austenite. From the viewpoint of ensuring a structure with appropriate nanohardness and making the solid solution carbon concentration in the retained austenite above a certain amount, the amount of Si is 0.01% or more, preferably 0.50% or more, and more preferably 0.80% or more.

[0053] On the other hand, when the amount of Si is too large, the concentration of dissolved carbon in the retained austenite increases excessively. Therefore, the amount of Si is 3.00% or less, preferably 2.60% or less, and more preferably 2.40% or less.

[0054] (Mn: 1.50~4.00%)

[0055] Mn affects the area ratio of tempered martensite and bainite. From the viewpoint of obtaining good impact resistance and a yield strength of 800 MPa or more, the amount of Mn is 1.50% or more, preferably 1.90% or more, and more preferably 2.30% or more.

[0056] On the other hand, when the amount of Mn is too much, the structure A with a nanohardness of 7 GPa or more, which becomes the starting point of cracks, increases, and the workability decreases. Therefore, the amount of Mn is 4.00% or less, preferably 3.50% or less, and more preferably 3.30% or less.

[0057] (P: 0.100% or less)

[0058] P segregates at the prior austenite grain boundaries and embrittles the grain boundaries. As a result, the ultimate deformation energy of the steel sheet decreases, and workability decreases. Therefore, the amount of P is 0.100% or less, preferably 0.030% or less, and more preferably 0.010% or less.

[0059] The lower limit of the amount of P is not particularly limited, but P is a solid solution strengthening element and increases the strength of the steel sheet, so it is preferably 0.001%, more preferably 0.002%, and even more preferably 0.003%.

[0060] (S: 0.0200% or less)

[0061] S combines with Mn to form coarse MnS, which becomes a starting point for cracks, thereby reducing workability. Therefore, the amount of S is 0.0200% or less, preferably 0.0100% or less, and more preferably 0.0020% or less.

[0062] The lower limit of the amount of S is not particularly limited, but is preferably 0.0001%, more preferably 0.0002%, and further preferably 0.0003% due to restrictions in production technology.

[0063] (Al: 0.100% or less)

[0064] Al increases the A3 transformation point. As a result, ferrite increases and the area ratio of tempered martensite and bainite decreases. Therefore, the amount of Al is 0.100% or less, preferably 0.080% or less, and more preferably 0.060% or less.

[0065] The lower limit of the amount of Al is not particularly limited, but is, for example, 0.010%, preferably 0.020%, from the viewpoint of suppressing the formation of carbides during heat treatment and promoting the formation of retained austenite.

[0066] (N: 0.0100% or less)

[0067] N combines with Ti to form TiN, which becomes a starting point of cracks, thereby reducing workability. Therefore, the amount of N is 0.0100% or less, preferably 0.0080% or less, and more preferably 0.0060% or less.

[0068] The lower limit of the amount of N is not particularly limited, but is preferably 0.0001%, more preferably 0.0003%, and further preferably 0.0005% due to restrictions in production technology.

[0069] (O: 0.0100% or less)

[0070] O forms oxides that serve as starting points for cracks, thereby reducing workability. Therefore, the amount of O is 0.0100% or less, preferably 0.0050% or less, and more preferably 0.0020% or less.

[0071] (Other elements)

[0072] The present component composition may further contain, in mass %, at least one element selected from the group consisting of the elements described below.

[0073] ((B: 0.0100% or less))

[0074] B is an element that can improve the hardenability of the steel sheet by segregating at the austenite grain boundary, and it is preferably added because it increases the yield strength of the steel sheet.

[0075] However, when the amount of B is too much, Fe 23 (CB) 6 becomes the starting point of cracks, and workability is reduced. Therefore, the amount of B is preferably 0.0100% or less, more preferably 0.0050% or less, further preferably 0.0040% or less, and particularly preferably 0.0030% or less.

[0076] The lower limit of the amount of B is not particularly limited, but from the viewpoint of obtaining the effect of adding B, it is, for example, 0.0005%, preferably 0.0010%.

[0077] ((Ti: 0.200% or less))

[0078] Ti forms fine carbides, nitrides, or carbonitrides during hot rolling or heat treatment, thereby increasing the yield strength of the steel sheet, and therefore, it is preferably added.

[0079] However, when the amount of Ti is too large, coarse nitrides formed by combining with N increase as crack starting points, thereby reducing workability. Therefore, the amount of Ti is preferably 0.200% or less, more preferably 0.100% or less, and further preferably 0.050% or less.

[0080] The lower limit of the amount of Ti is not particularly limited, but from the viewpoint of obtaining the effect of adding Ti, it is, for example, 0.005%, preferably 0.010%.

[0081] ((Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less))

[0082] Nb, V, and W form fine carbides, nitrides, or carbonitrides during hot rolling or heat treatment, thereby increasing the yield strength of the steel sheet, and therefore, are preferably added.

[0083] However, when these elements are added in excessive amounts, they do not melt when the steel billet is heated and remain as coarse carbides. Coarse carbides become the starting point of cracks and reduce workability. Therefore, the amount of Nb is preferably 0.200% or less, more preferably 0.100% or less, and further preferably 0.050% or less. The lower limit is not particularly limited, and from the viewpoint of obtaining the effect of Nb addition, it is, for example, 0.005%, preferably 0.010%.

[0084] The amount of V is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of V addition, it is, for example, 0.005%, preferably 0.010%.

[0085] The amount of W is preferably 0.100% or less, more preferably 0.080% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of W addition, it is, for example, 0.010%, preferably 0.020%.

[0086] ((Mo: 1.000% or less, Cr: 1.000% or less))

[0087] Mo and Cr are preferably added because they increase the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of these elements is too large, hard martensite is excessively generated, the starting point of cracks increases, and thus the workability decreases.

[0088] Therefore, the amount of Mo is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Mo addition, it is, for example, 0.010%, preferably 0.020%.

[0089] The Cr content is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Cr addition, it is, for example, 0.010%, preferably 0.020%.

[0090] ((Sb: 0.200% or less, Sn: 0.200% or less))

[0091] Sb and Sn are preferably added because they suppress decarburization on the surface of the steel sheet and increase the yield strength of the steel sheet. However, when the amount of these elements is too large, the steel becomes brittle and the workability decreases.

[0092] Therefore, the amount of Sb is preferably 0.200% or less, more preferably 0.080% or less, and still more preferably 0.040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Sb addition, it is, for example, 0.001%, preferably 0.002%.

[0093] The amount of Sn is preferably 0.200% or less, more preferably 0.080% or less, and still more preferably 0.040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Sn addition, it is, for example, 0.001%, preferably 0.002%.

[0094] ((Zr: 0.1000% or less, Te: 0.100% or less))

[0095] Zr and Te make the shapes of nitrides and sulfides spherical and improve workability, so they are preferably added. However, when the amount of these elements is too large, coarse precipitates that remain without solid solution during heating of the hot-rolled steel slab increase, and workability deteriorates.

[0096] Therefore, the amount of Zr is preferably 0.1000% or less, more preferably 0.0800% or less, and still more preferably 0.0500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding Zr, it is, for example, 0.0050%, preferably 0.0100%.

[0097] The amount of Te is preferably 0.100% or less, more preferably 0.080% or less, and still more preferably 0.050% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding Te, it is, for example, 0.005%, preferably 0.010%.

[0098] (Cu: 1.000% or less)

[0099] Cu is preferably added because it increases the yield strength of the steel sheet by improving the hardenability of the steel sheet. However, when the amount of Cu is too large, the workability deteriorates due to the increase in Cu inclusions.

[0100] Therefore, the amount of Cu is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Cu addition, it is, for example, 0.010%, preferably 0.020%.

[0101] ((Ni: 1.000% or less))

[0102] Ni is preferably added because it improves the hardenability of the steel sheet and increases the yield strength of the steel sheet. However, when the amount of Ni is too large, the workability deteriorates due to an increase in hard martensite.

[0103] Therefore, the amount of Ni is preferably 1.000% or less, more preferably 0.800% or less, and still more preferably 0.500% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ni addition, it is, for example, 0.010%, preferably 0.020%.

[0104] (Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less))

[0105] Ca, Mg and REM (Rare Earth Metal) are preferably added because they spheroidize the shape of precipitates such as sulfides and oxides and improve workability. However, when the amount of these elements is too large, coarsened sulfides become the starting point of cracks, and workability deteriorates.

[0106] Therefore, the amount of Ca is preferably 0.0100% or less, more preferably 0.0050% or less, and still more preferably 0.0040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ca addition, it is, for example, 0.0005%, preferably 0.0010%.

[0107] The amount of Mg is preferably 0.0100% or less, more preferably 0.0050% or less, and still more preferably 0.0040% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Mg addition, it is, for example, 0.0005%, preferably 0.0010%.

[0108] The amount of REM is preferably 0.0100% or less, more preferably 0.0040% or less, and still more preferably 0.0030% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding REM, it is, for example, 0.0005%, preferably 0.0010%.

[0109] ((Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, Bi: 0.200% or less))

[0110] Co, Ta, Hf and Bi are preferably added because they spheroidize the shape of precipitates and improve workability. However, when the amount of these elements is too large, coarsened precipitates become the starting point of cracks, and workability deteriorates.

[0111] Therefore, the amount of Co is preferably 0.010% or less, more preferably 0.008% or less, and still more preferably 0.007% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Co addition, it is, for example, 0.001%, preferably 0.002%.

[0112] The amount of Ta is preferably 0.10% or less, more preferably 0.08% or less, and still more preferably 0.07% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Ta addition, it is, for example, 0.01%, preferably 0.02%.

[0113] The amount of Hf is preferably 0.10% or less, more preferably 0.08% or less, and still more preferably 0.07% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of Hf addition, it is, for example, 0.01%, preferably 0.02%.

[0114] The Bi content is preferably 0.200% or less, more preferably 0.100% or less, and still more preferably 0.080% or less. The lower limit is not particularly limited, but from the viewpoint of obtaining the effect of adding REM, it is, for example, 0.001%, preferably 0.005%.

[0115] (margin)

[0116] The balance in this component composition is composed of Fe and inevitable impurities.

[0117] Microstructure

[0118] Next, the microstructure of the steel sheet included in the present high-strength steel sheet (hereinafter, also referred to as “the present microstructure” for convenience) will be described.

[0119] In order to obtain the effects of the present invention, it is not sufficient to satisfy only the above-mentioned present component composition, and it is also necessary to satisfy the present microstructure described below.

[0120] Hereinafter, the area ratio refers to the area ratio relative to the entire microstructure. The area ratio of each structure is obtained by the method described in the Examples described below.

[0121] (Total area ratio of tempered martensite and bainite: 55-95%)

[0122] From the viewpoint of stably ensuring good impact resistance and yield strength, the total area ratio of tempered martensite and bainite is 55% or more, preferably 58% or more, and more preferably 60% or more.

[0123] On the other hand, when the total area ratio of tempered martensite and bainite is too high, the structure A having a nanohardness of 7 GPa or more increases, the abundance ratio (A / B) of the structure A to the structure B becomes too large, and the workability deteriorates.

[0124] Therefore, the total area ratio is 95% or less, preferably 92% or less, and more preferably 88% or less.

[0125] (Existence ratio A / B: 0.8 to 2.5)

[0126] The structure A having a nanohardness of 7 GPa or more is fine and hard, and improves the crack arrestability by inhibiting the progress of cracks generated by external force during collision.

[0127] On the other hand, the structure B having a nanohardness of 6 GPa or less has high toughness, and thus improves the processability.

[0128] By appropriately controlling the abundance ratio (A / B) of structure A to structure B, both the crack arrestability and the processability are excellent.

[0129] From the perspective of excellent crack arrestability, the presence ratio (A / B) is 0.8 or more, preferably 1.0 or more, and more preferably 1.1 or more.

[0130] On the other hand, when the existence ratio (A / B) of structure A to structure B is too large, the structure A having a nanohardness of 7 GPa or more becomes the starting point of cracks, and the workability is deteriorated. Therefore, the existence ratio (A / B) is 2.5 or less, preferably 2.3 or less, and more preferably 2.0 or less.

[0131] Nanohardness is hardness measured using a nanoindentation method, and is specifically determined by the method described in Examples described below.

[0132] The plastic deformation resistance in a local region of a tissue at a submicron level cannot be evaluated using hardness other than nanohardness (eg, Vickers hardness).

[0133] (Concentration of dissolved carbon in retained austenite: 0.50 to 0.90 mass%)

[0134] This microstructure contains retained austenite.

[0135] When the concentration of dissolved carbon in retained austenite increases, the hardness of martensite transformed from retained austenite significantly increases when stress is repeatedly applied, so that crack starting points increase and workability deteriorates.

[0136] Therefore, the dissolved carbon concentration in the retained austenite is 0.90 mass % or less, preferably 0.85 mass % or less, and more preferably 0.80 mass %.

[0137] On the other hand, when the dissolved carbon concentration in the retained austenite is too low, the workability decreases.

[0138] Therefore, the concentration of dissolved carbon in the retained austenite is 0.50 mass % or more, preferably 0.60 mass % or more, and more preferably 0.70 mass % or more.

[0139] (Residual Organization)

[0140] The present microstructure may include structures other than tempered martensite, bainite and retained austenite (remaining structure).

[0141] Examples of the residual structure include fresh martensite, pearlite, ferrite, iron-based carbonitrides, alloy carbonitrides, inclusions such as MnS and Al2O3, and other known structures.

[0142] The area ratio of the surplus structure is preferably 20% or less, more preferably 10% or less, and further preferably 5% or less. When the area ratio of the surplus structure is within this range, the effect of the present invention is not impaired.

[0143] 《Diffusible hydrogen content in steel: 0.50 mass ppm or less》

[0144] If the amount of diffusible hydrogen in steel is too high, delayed fracture occurs and workability deteriorates. Therefore, the amount of diffusible hydrogen in steel is 0.50 mass ppm or less, preferably 0.30 mass ppm or less, and more preferably 0.20 mass ppm or less.

[0145] The amount of diffusible hydrogen in the steel is determined by the method described in the examples described later.

[0146] <Plating>

[0147] From the viewpoint of improving corrosion resistance and the like, the high-strength steel sheet may further include a plating layer on the surface of the steel sheet.

[0148] Examples of the plating layer include a hot-dip galvanizing layer, an alloyed hot-dip galvanizing layer, and an electrogalvanizing layer. The plating layer is formed by a plating treatment described below.

[0149] [Method for producing high-strength steel sheet]

[0150] Next, a method for producing a high-strength steel sheet according to the present embodiment (hereinafter referred to as "the present production method") will be described. The present production method is also a method for producing the above-mentioned present high-strength steel sheet.

[0151] Unless otherwise specified, the temperature when heating or cooling the steel billet, steel plate, etc. shown below refers to the surface temperature of the steel billet, steel plate, etc.

[0152] The method for producing molten steel to become a steel billet (steel raw material) is not particularly limited, and a known method using a converter, an electric furnace, etc. can be adopted. Preferably, the steel billet is obtained from the molten steel by a continuous casting method. The steel billet can also be obtained by other methods such as an ingot casting-blowing rolling method and a thin slab continuous casting method.

[0153] <Hot rolling>

[0154] In the present production method, first, a steel slab having the above-mentioned present component composition is hot-rolled to obtain a hot-rolled steel sheet.

[0155] When hot rolling is performed, the steel slab may be reheated in a heating furnace before rolling. When the steel slab is kept at a temperature higher than a predetermined temperature, direct rolling may be performed without heating the steel slab.

[0156] In hot rolling, the steel slab is subjected to rough rolling and finish rolling.

[0157] It is preferred that the steel slab be heated before rough rolling to melt the carbides in the steel slab.

[0158] From the viewpoint of dissolving carbides or preventing an increase in rolling load, the temperature at which the billet is heated (billet heating temperature) is preferably 1100° C. or higher, more preferably 1150° C. or higher.

[0159] On the other hand, from the viewpoint of preventing an increase in scale loss, the slab heating temperature is preferably 1300° C. or lower, more preferably 1280° C. or lower.

[0160] As described above, when the steel slab before rough rolling is maintained at a temperature equal to or higher than a predetermined temperature and carbides in the steel slab are melted, heating of the steel slab before rough rolling can be omitted.

[0161] The conditions for rough rolling and finish rolling are not particularly limited. For example, the finish rolling end temperature is preferably 700 to 1100°C, more preferably 800 to 1000°C.

[0162] <Cold Rolling>

[0163] Next, the hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet.

[0164] The rolling reduction rate of cold rolling is preferably 30% or more, more preferably 35% or more. The upper limit is not particularly limited, but is, for example, 70% or less, preferably 65% ​​or less.

[0165] <Heat Treatment>

[0166] Next, the cold-rolled steel sheet obtained by cold rolling is subjected to heat treatment.

[0167] Figure 1 This is a diagram showing an example of heat treatment.

[0168] In the heat treatment, in short, the cold-rolled steel sheet is heated at a heating temperature T1, cooled to a cooling stop temperature T2, and then reheated to a reheating temperature T3, and recooled without being held at the reheating temperature T3. During the recooling, the cold-rolled steel sheet is held at a temperature T4 lower than the reheating temperature T3.

[0169] In addition, the cold-rolled steel sheet which has been subjected to heat treatment and further subjected to temper rolling described later corresponds to the steel sheet included in the above-mentioned present high-strength steel sheet.

[0170] 《Heating temperature T1: 750~950℃, heating time t1: 10~500s》

[0171] First, the cold-rolled steel sheet is heated at a heating temperature T1.

[0172] At this time, if the heating temperature T1 is too low or the heating time t1 (the time the cold-rolled steel sheet is kept at the heating temperature T1) is too short, heating in the dual phase region of ferrite and austenite is achieved. In this case, the final microstructure contains ferrite, and the total area ratio of tempered martensite and bainite is reduced.

[0173] Therefore, the heating temperature T1 is 750° C. or higher, preferably 800° C. or higher, and more preferably 850° C. or higher. The heating time t1 is 10 s or higher, preferably 50 s or higher, and more preferably 80 s or higher.

[0174] On the other hand, when the heating temperature T1 is too high or the heating time t1 is too long, the amount of hydrogen intruding into the steel increases due to the increase in hydrogen partial pressure, so the amount of diffusible hydrogen in the steel increases.

[0175] In addition, the total area ratio of tempered martensite and bainite increases, the existence ratio (A / B) becomes too large, and the workability deteriorates.

[0176] Therefore, the heating temperature T1 is 950° C. or less, preferably 930° C. or less, and more preferably 900° C. or less. The heating time t1 is 500 s or less, preferably 300 s or less, and more preferably 200 s or less.

[0177] 《Cooling stop temperature T2: 120℃ or higher and lower than 280℃》

[0178] Next, the cold-rolled steel sheet heated at the heating temperature T1 is cooled to a cooling stop temperature T2.

[0179] When the cooling stop temperature T2 is too low, the total area ratio of tempered martensite and bainite increases, and the presence ratio (A / B) becomes too large, so that the workability deteriorates.

[0180] Therefore, the cooling stop temperature T2 is 120°C or higher, preferably 140°C or higher, and more preferably 150°C or higher.

[0181] On the other hand, when the cooling stop temperature T2 is too high, the total area ratio of tempered martensite and bainite decreases. In addition, the structure B with a nanohardness of 6 GPa or less increases, the existence ratio (A / B) becomes too small, and the crack arrestability deteriorates.

[0182] Therefore, the cooling stop temperature T2 is lower than 280°C, preferably 270°C or lower, and more preferably 260°C or lower.

[0183] 《Reheating temperature T3》

[0184] Next, the cold-rolled steel sheet cooled to the cooling stop temperature T2 is reheated to the reheating temperature T3, and is recooled without being held at the reheating temperature T3.

[0185] The reheating temperature T3 is not particularly limited as long as it satisfies a heat input influence index J described later.

[0186] The reheating temperature T3 is, for example, 280° C. or higher, preferably 290° C. or higher, and more preferably 300° C. or higher.

[0187] On the other hand, the reheating temperature T3 is, for example, 400° C. or lower, preferably 380° C. or lower, and more preferably 350° C. or lower.

[0188] 《Heat input impact index J: 1500~4000》

[0189] The heat input influence index J from the cooling stop temperature T2 to the reheating temperature T3 of the cold-rolled steel sheet is represented by the following formula (1).

[0190] J = (T3-T2)(log(9t)+20) …(1)

[0191] In the above formula (1), t is the heating time (unit: s) from the cooling stop temperature T2 to the reheating temperature T3°C.

[0192] The nanohardness of each structure constituting the microstructure changes according to the state of carbon in each structure. The heat input influence index J affects not only the state of carbon but also the diffusion speed and location of carbon.

[0193] When the heat input influence index J is too low, carbon in the structure exists in the form of solid solution, so the structure A with a nanohardness of 7 GPa or more increases, the existence ratio (A / B) becomes too large, and the workability deteriorates. In addition, the solid solution carbon concentration in the retained austenite becomes too high, and the workability deteriorates.

[0194] Therefore, the heat input influence index J is 1500 or more, preferably 1800 or more, and more preferably 2000 or more.

[0195] On the other hand, when the heat input influence index J is too high, the carbon in the structure exists in the form of carbides, so the structure B with a nanohardness of less than 6 GPa increases, the existence ratio (A / B) becomes too small, and the crack arrestability deteriorates. In addition, the solid solution carbon concentration in the retained austenite becomes too low, and the workability deteriorates.

[0196] Therefore, the heat input influence index J is 4000 or less, preferably 3800 or less, and more preferably 3500 or less.

[0197] 《Holding time t4 at temperature T4 lower than reheating temperature T3: 1s or more》

[0198] During the re-cooling, the cold-rolled steel sheet is held at a temperature T4 lower than the reheating temperature T3.

[0199] When the temperature T4 is equal to or higher than the reheating temperature T3, the existence ratio (A / B) becomes too small, and the crack arrestability deteriorates.

[0200] The lower limit of the temperature T4 is not particularly limited, but is, for example, 180°C, preferably 200°C, and more preferably 220°C.

[0201] When the cold-rolled steel sheet is not held at the temperature T4 (for example, the holding time t4 at the temperature T4 is zero), the ratio (A / B) becomes too large, and workability may deteriorate.

[0202] Therefore, the holding time t4 is 1 s or longer, preferably 3 s or longer, and more preferably 5 s or longer.

[0203] <Surface temper rolling>

[0204] Next, the cold-rolled steel sheet subjected to the heat treatment (specifically, maintained at the temperature T4 for 1 second or longer) is temper-rolled using rolls.

[0205] 《Roller surface roughness: 1.5~5.0μm》

[0206] By controlling the surface roughness of the roller, the movable dislocation introduced into the local area at the submicron level is adjusted, and the hardness distribution of the structure is controlled.

[0207] If the surface roughness of the roller is too small, the existence ratio (A / B) becomes too small, and the crack arrestability deteriorates. Therefore, the surface roughness of the roller is 1.5 μm or more, preferably 1.8 μm or more, and more preferably 2.0 μm or more.

[0208] On the other hand, if the surface roughness of the roller is too large, the presence ratio (A / B) becomes too large, and the workability deteriorates. Therefore, the surface roughness of the roller is 5.0 μm or less, preferably 4.5 μm or less, and more preferably 4.0 μm or less.

[0209] The surface roughness of the roller is the arithmetic mean roughness Ra measured in accordance with JIS B 0601.

[0210] <Plating treatment>

[0211] In the present production method, a plating layer can be formed on the surface of a cold-rolled steel sheet subjected to temper rolling by subjecting the cold-rolled steel sheet to plating treatment.

[0212] Examples of the plating layer include a hot-dip galvanizing layer, an alloyed hot-dip galvanizing layer, and an electrogalvanizing layer.

[0213] The plating treatment is preferably hot-dip galvanizing, alloy hot-dip galvanizing or electrogalvanizing.

[0214] When hot-dip galvanizing is performed, for example, the steel sheet is immersed in a zinc bath at a bath temperature of 440 to 500° C. Then, the coating weight is preferably adjusted by gas wiping or the like.

[0215] The zinc bath preferably has a composition in which the Al content is 0.10 to 0.23% by mass and the balance is Zn and unavoidable impurities.

[0216] When performing alloying hot-dip galvannealing, when the alloying temperature is too low, the Zn-Fe alloying rate sometimes becomes too slow, and alloying becomes significantly difficult. On the other hand, when the alloying temperature is too high, the untransformed austenite sometimes transforms into pearlite. Therefore, the alloying temperature is preferably 450 to 600°C, more preferably 470 to 550°C, and further preferably 470 to 530°C.

[0217] The electrogalvanizing treatment is performed to form an electrogalvanized layer.

[0218] The electrogalvanized layer is not particularly limited, and a conventionally known electrogalvanized layer is preferably used. The electrogalvanized layer may be a zinc alloy plating layer in which an appropriate amount of Fe, Cr, Ni, Mn, Co, Sn, Pb, or Mo is added to Zn according to the purpose.

[0219] The coating weight of hot-dip galvanized steel sheet (GI), alloyed hot-dip galvanized steel sheet (GA) and electrogalvanized steel sheet (EG) is preferably 20 to 80 g / m per side. 2 (Both sides plated).

[0220] The plated steel sheet is cooled to a temperature of, for example, 50° C. or less. The steel sheet cooled to a temperature of 50° C. or less may be rolled at an elongation of 0.05 to 1.00%. The elongation is preferably 0.08 to 0.70%.

[0221] The rolling can be carried out on a device that is continuous with a device (plating device) for implementing a galvanizing treatment, or on a device that is discontinuous with the plating device. In addition, the target elongation can be achieved by one rolling, or the target elongation can be achieved by rolling twice or more.

[0222] In addition, the rolling described here generally refers to skin temper rolling, but as long as the same elongation as skin temper rolling can be given, rolling by processing using a leveler or the like may also be used.

[0223] In the present manufacturing method, for example, the holding temperature such as the heating temperature and the reheating temperature may not be constant as long as they are within the above temperature range. The cooling rate may also be changed during cooling as long as it is within the above speed range. As long as the above temperature range and other conditions are met, the heat treatment may be performed with any equipment.

[0224] [member]

[0225] Next, the components of the present embodiment (hereinafter also referred to as “present components”) will be described.

[0226] The present member is a member at least partly formed using the present high-strength steel sheet described above, and is, for example, a member formed by forming the present high-strength steel sheet into a target shape by processing (press processing, etc.).

[0227] The present member is preferably an automobile component. It should be noted that the automobile component may include a steel sheet other than the present high-strength steel sheet as a raw material.

[0228] As described above, the high-strength steel sheet has a yield strength of 800 MPa or more and is excellent in processability, collision resistance and crack arrest. Therefore, the member has excellent processability, collision resistance and crack arrest, and can contribute to the lightweight of the vehicle body. Therefore, among automobile parts, it is particularly suitable as all members used in automobile skeleton structural parts or automobile reinforcement parts.

[0229] [Method of manufacturing component]

[0230] Next, a method for producing the present member will be described.

[0231] The present member is obtained, for example, by subjecting the present high-strength steel sheet to at least one of a forming process and a joining process.

[0232] The forming process is not particularly limited, and examples thereof include press working and the like.

[0233] The joining process is not particularly limited, and examples thereof include general welding such as spot welding and arc welding, and riveting using rivets or the like.

[0234] Example

[0235] Hereinafter, the present invention will be described in detail with reference to Examples, but the present invention is not limited to the Examples described below.

[0236] <Manufacturing of Steel Plate>

[0237] Molten steel having the composition shown in Table 1 below, with the balance being Fe and inevitable impurities, was produced by a converter, and steel slabs were obtained by continuous casting. The underlined parts in Table 1 below are outside the scope of the present invention (the same applies to Tables 2 and 3 described below).

[0238] The obtained steel slab was hot rolled under the conditions shown in the following Table 2 to obtain a hot rolled steel sheet. Specifically, the steel slab was heated to 1250°C, rough rolled, and then finish rolled at a finish rolling end temperature of 900°C.

[0239] The obtained hot-rolled steel sheets were cold-rolled at the rolling ratios shown in Table 2 below, thereby obtaining cold-rolled steel sheets (sheet thickness: 1.2 mm).

[0240] The obtained cold-rolled steel sheets were subjected to heat treatment under the conditions shown in Table 2 below.

[0241] Furthermore, the cold-rolled steel sheets subjected to the heat treatment were subjected to temper rolling under the conditions shown in Table 2 below.

[0242] In some examples, both surfaces of a cold-rolled steel sheet (CR) after temper rolling are plated to obtain a galvanized steel sheet (GI), a galvannealed steel sheet (GA), or an electrogalvanized steel sheet (EG).

[0243] As the hot-dip galvanizing bath, a zinc bath containing Al: 0.20 mass % and the balance consisting of Zn and inevitable impurities is used when manufacturing GI, and a zinc bath containing Al: 0.14 mass % and the balance consisting of Zn and inevitable impurities is used when manufacturing GA.

[0244] The bath temperature was set to 470° C. in the case of producing both GI and GA.

[0245] The coating weight is set to 45 to 72 g / m per side when manufacturing GI. 2 When manufacturing GA, set it to 45g / m per single side. 2 .

[0246] In the case of producing GA, the alloying temperature was set to 500°C.

[0247] The composition of the GI plating layer contains Fe: 0.1-1.0 mass%, Al: 0.2-1.0 mass%, and the balance is Fe and inevitable impurities. The composition of the GA plating layer contains Fe: 7-15 mass%, Al: 0.1-1.0 mass%, and the balance is Fe and inevitable impurities.

[0248] When manufacturing EG, an electrogalvanizing line is used with a coating weight of 30 g / m per side. 2 The electro-galvanizing treatment is carried out by

[0249] Hereinafter, the cold-rolled steel sheet (CR), the hot-dip galvanized steel sheet (GI), the alloyed hot-dip galvanized steel sheet (GA) and the electrogalvanized steel sheet (EG) after heat treatment are also referred to as "steel sheets".

[0250] <Observation of Microstructure>

[0251] The microstructure of the obtained steel plate was observed as follows. The results are shown in the following Table 3. In addition, in the following Table 3, martensite is expressed as "M", bainite is expressed as "B", and austenite is expressed as "γ".

[0252] 《Total area ratio of tempered martensite and bainite》

[0253] The obtained steel plate was polished so that the cross section (L cross section) at the 1 / 4 position of the plate thickness and parallel to the rolling direction was used as the observation surface. The observation surface was corroded with 1 vol % nitric acid solution and observed with a scanning electron microscope (SEM) at a magnification of 3000 times.

[0254] The observation surface was observed in 10 fields to obtain a SEM image, and the obtained SEM image was analyzed to determine the total area ratio (unit: %) of tempered martensite and bainite.

[0255] More specifically, dark gray portions in the obtained SEM images were determined to be tempered martensite and bainite, and their area ratios (average area ratios of 10 fields of view) were determined. In the analysis of the SEM images, Image-Pro manufactured by MediaCybernetics was used as analysis software.

[0256] 《Determination of Nanohardness》

[0257] The obtained steel plate was polished so that the cross section (L cross section) at the position of 1 / 4 of the plate thickness and parallel to the rolling direction was the observation surface. The observation surface was mirror-polished using diamond paste, and then buff-polished using colloidal silica.

[0258] The nanohardness of the observation surface was measured at 225 points using a nanoindentation device equipped with a Bosch indenter.

[0259] As measurement conditions, the loading speed and the unloading speed were set to 50 μN / s, the maximum load was set to 500 μN, the data collection interval was set to 5 ms, and the distance between indentations was set to 2 μm or more.

[0260] Among the 225 measurement points, the measurement points with nanohardness of 7 GPa or more were defined as structure A, and the measurement points with nanohardness of 6 GPa or less were defined as structure B. The ratio of the number of measurement points was calculated as the abundance ratio of structure A to structure B (A / B).

[0261] 《Determination of dissolved carbon concentration in retained austenite》

[0262] The obtained steel plate was ground so that the position of 1 / 4 of the plate thickness was used as an observation surface, and was further ground by 0.1 mm by chemical polishing.

[0263] For the observed surface, an X-ray diffraction (XRD) device was used with CoKα as the X-ray source to obtain the peak angles of the (200) plane, (220) plane, and (311) plane of austenite, and the lattice constant a (unit: Å) of retained austenite was calculated by the following formula (2).

[0264] The calculated lattice constant a of retained austenite is substituted into the following formula (3) to determine the content (unit: mass %) of carbon (C) in the retained austenite, which is taken as the solid solution carbon concentration in the retained austenite.

[0265] a=1.79021√2 / sinθ …(2)

[0266] a=3.572+0.0012[Mn]-0.00157[Si]+0.0056[Al]+0.033[C] …(3)

[0267] In formula (2), a is the lattice constant of retained austenite (unit: Å), and θ is the value obtained by dividing the diffraction peak angle of the (220) plane by 2 (unit: rad).

[0268] In formula (3), a is the lattice constant of retained austenite (unit: Å), and [M] is the content of element M in retained austenite (unit: mass %). As the content of element M other than C, the content of each element in the overall component composition of the steel plate (specifically, for example, the above-mentioned present component composition) is used.

[0269] <Determination of Diffusible Hydrogen Amount in Steel>

[0270] A test piece with a length of 30 mm and a width of 5 mm was cut from the obtained steel plate. The amount of diffusible hydrogen in the steel was measured by the temperature rise desorption analysis method for the cut test piece. The heating rate was set to 200°C / hour. The cumulative value of the amount of hydrogen detected in the temperature range from room temperature (25°C) to below 210°C was taken as the amount of diffusible hydrogen in the steel (unit: mass ppm).

[0271] The plated steel sheet was measured in the same manner after the plated steel sheet was removed using a router (precision grinder).

[0272] The results are shown in the following Table 3. The amount of diffusible hydrogen in the steel is preferably 0.50 mass ppm or less.

[0273] <Evaluation>

[0274] The obtained steel sheets were evaluated by the following methods. The results are shown in Table 3 below.

[0275] Tensile test

[0276] From the obtained steel plate, a No. 5 test piece described in JIS Z 2241 was cut out with the direction at 90° to the rolling direction as the longitudinal direction (tensile direction). Using the cut test piece, a tensile test according to JIS Z 2241 was performed 5 times, and the yield strength (YS) and elongation (El) were calculated from the average values ​​of the 5 times.

[0277] When YS is 800 MPa or more, it can be evaluated as high strength.

[0278] When El is 8.0% or more, it can be evaluated that the ductility is good and the workability is excellent.

[0279] 《Collision Endurance Evaluation Test》

[0280] A member (hat member) having a hat-shaped cross section was produced using the obtained steel plate, and a three-point bending test was performed to determine the maximum load (unit: kN).

[0281] First, based on Figure 2A , the cap member 1 is described.

[0282] Figure 2A 2 is a cross-sectional view showing the cap member 1 . Figure 2A , the dimensions of the cap member 1 are shown. The cap member 1 is joined to the flat plate 2 by spot welding (nugget diameter: 4.5√t, spot spacing: 35 mm). The flat plate 2 is a cold-rolled steel plate without coating, with a tensile strength (TS) of 590 MPa and a plate thickness t that is the same as that of the cap member 1 (1.2 mm).

[0283] Next, based on Figure 2B , the three-point bending test is explained.

[0284] Figure 2B 1 is a schematic diagram showing the cap member 1 subjected to a three-point bending test. Figure 2B Various dimensions are also shown in FIG. The flat plate 2 joined to the cap member 1 is supported by the support member 3 as a rigid body. In this state, the impactor 4 as a rigid body is moved from above toward the cap member 1 at a speed of 1 m / s. In this way, a three-point bending test is implemented.

[0285] The three-point bending test was performed three times on each steel plate, and the average value of the maximum loads obtained each time was taken as the maximum load of the steel plate.

[0286] In the following Table 3, the case where the maximum load was 40 kN or more was described as "◎", the case where the maximum load was 30 kN or more and less than 40 kN was described as "○", and the case where the maximum load was less than 30 kN was described as "×".

[0287] If it is "◎" or "○", it can be evaluated that the collision resistance is excellent.

[0288] 《Crack arrest evaluation test》

[0289] The obtained steel plate was bent using a 90-degree V-block under the following test conditions to obtain a test piece. The ridgeline of the bending vertex in the obtained test piece was observed at a magnification of 40 times using a digital microscope (RH-2000, manufactured by HIROX Corporation) to measure the length of the crack. In the case of multiple cracks, the total length of the cracks was calculated.

[0290] In Table 3 below, the case where the total length of cracks was 6000 μm or less was indicated as “◎”, the case where the total length of cracks was greater than 6000 μm and less than 12000 μm was indicated as “○”, and the case where the total length of cracks was greater than 12000 μm was indicated as “×”.

[0291] If it is "◎" or "○", it can be evaluated that the crack arrestability is excellent.

[0292] (Test conditions)

[0293] Test method: Roller support, punch press

[0294] Roller diameter: φ30mm

[0295] Punch tip R: 0.4mm

[0296] Distance between rollers: (plate thickness × 2) + 0.5 mm

[0297] Stroke speed: 20mm / min

[0298] Test piece size: 60mm×60mm

[0299] Bending direction: Rolling right angle method

[0300]

[0301]

[0302] [Table 2]

[0303]

[0304]

[0305] [Table 3]

[0306]

[0307]

[0308] <Summary of evaluation results>

[0309] As shown in Tables 1 to 3, the steel plates Nos. 1 to 3, 5 to 6, 10, 15 to 17, 22, 30, and 33 to 42 all have a yield strength of 800 MPa or more and are excellent in workability, impact resistance, and crack arrestability.

[0310] On the other hand, the steel sheets of Nos. 4, 7 to 9, 11 to 14, 18 to 21, 23 to 29, and 31 to 32 were insufficient in at least one of the yield strength, workability, impact resistance, and crack arrestability.

Claims

1. A high-strength steel plate comprising: The steel plate has a diffusible hydrogen content of 0.50 mass ppm or less. The steel plate has a composition and a microstructure, The composition contains, in mass%, C: 0.150-0.500%, Si: 0.01-3.00%, Mn: 1.50-4.00%, P: 0.100% or less, S: 0.0200% or less, Al: 0.100% or less, N: 0.0100% or less, and O: 0.0100% or less, with the balance being Fe and inevitable impurities. In the microstructure, the total area ratio of tempered martensite and bainite is 55 to 95%, the abundance ratio A / B of structure A with a nanohardness of 7 GPa or more and structure B with a nanohardness of 6 GPa or less is 0.8 to 2.5, and the dissolved carbon concentration in the retained austenite is 0.50 to 0.90 mass %.

2. The high-strength steel plate according to claim 1, wherein: The composition further comprises, by mass%, B selected from: At least one element selected from the group consisting of Ti: 0.0100% or less, Ti: 0.200% or less, Nb: 0.200% or less, V: 0.200% or less, W: 0.100% or less, Mo: 1.000% or less, Cr: 1.000% or less, Sb: 0.200% or less, Sn: 0.200% or less, Zr: 0.1000% or less, Te: 0.100% or less, Cu: 1.000% or less, Ni: 1.000% or less, Ca: 0.0100% or less, Mg: 0.0100% or less, REM: 0.0100% or less, Co: 0.010% or less, Ta: 0.10% or less, Hf: 0.10% or less, and Bi: 0.200% or less.

3. The high-strength steel sheet according to claim 1 or 2, wherein: The surface of the steel plate is also provided with a coating.

4. The high-strength steel plate according to claim 3, wherein: The coating is a hot-dip galvanized layer, an alloyed hot-dip galvanized layer or an electro-galvanized layer.

5. A method for producing a high-strength steel sheet, which is a method for producing the high-strength steel sheet according to claim 1, wherein: A steel slab having the component composition described in claim 1 is hot-rolled to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950° C. for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120° C. or higher and lower than 280° C., then heated to a reheating temperature T3, then recooled without being held at the reheating temperature T3, and held at a temperature T4 lower than the reheating temperature T3 for more than 1 second. The heat input influence index J from the cooling stop temperature T2 to the reheating temperature T3 represented by the following formula (1) is 1500 to 4000, The cold-rolled steel sheet maintained at the temperature T4 is subjected to temper rolling using a roller having a surface roughness of 1.5 to 5.0 μm. J = (T3-T2)(log(9t)+20) …(1) In the above formula (1), t is the heating time from the cooling stop temperature T2 to the reheating temperature T3°C, and the unit is s.

6. A method for producing a high-strength steel sheet, which is a method for producing the high-strength steel sheet according to claim 2, wherein: A steel slab having the component composition described in claim 2 is hot-rolled to obtain a hot-rolled steel sheet. The hot-rolled steel sheet is cold-rolled to obtain a cold-rolled steel sheet. The cold-rolled steel sheet is heated at a heating temperature T1 of 750 to 950° C. for 10 to 500 seconds, cooled to a cooling stop temperature T2 of 120° C. or higher and lower than 280° C., then heated to a reheating temperature T3, then recooled without being held at the reheating temperature T3, and held at a temperature T4 lower than the reheating temperature T3 for more than 1 second. The heat input influence index J from the cooling stop temperature T2 to the reheating temperature T3 represented by the following formula (1) is 1500 to 4000, The cold-rolled steel sheet maintained at the temperature T4 is subjected to temper rolling using a roller having a surface roughness of 1.5 to 5.0 μm. J = (T3-T2)(log(9t)+20) …(1) In the above formula (1), t is the heating time from the cooling stop temperature T2 to the reheating temperature T3°C, and the unit is s.

7. The method for producing a high-strength steel sheet according to claim 5 or 6, wherein: The cold-rolled steel sheet is subjected to a plating treatment.

8. The method for producing a high-strength steel sheet according to claim 7, wherein: The plating treatment is hot-dip galvanizing, alloyed hot-dip galvanizing or electro-galvanizing. 9 . A member formed using the high-strength steel sheet according to claim 1 .

10. A method for manufacturing a component, wherein: A member is obtained by subjecting the high-strength steel sheet according to any one of claims 1 to 4 to at least one of a forming process and a joining process.

Citation Information

Patent Citations

  • High strength steel sheet and manufacturing method therefor

    JP2017214647A

  • High strength steel sheet and manufacturing method therefor

    JP2018021231A

  • High strength steel sheet and manufacturing method therefor

    JP2018021233A